Bunge vs. Bhaskar: Några kritiska reflektioner kring ”nya” teoriers originalitet (Sociologisk Forskning, 1999)
Bunge vs. Bhaskar. Some critical reflections of the originality in new theoriesThis article takes its point of departure in the issue of the originality in new theories. By a comparative analysis of the thesis in Mario Bunge’s ”Causality” and Roy Bhaskar’s ”A Realist Theory of Science”, it is argued that many of the key concepts in the critical realist philosophy has a history that goes beyond that of Roy Bhaskar’s prominent book. The key-concepts that are compared are ”emergence”, ”the transitive and intransitive dimensions of science”, ”transfactuality” and ”the epistemic fallacy”. The analysis shows that the meaning of the concepts has been used and referred to in texts written earlier than ”A Realist Theory of Science”. The conclusion of the article is that none of the key-concepts discussed has its origin in ”A Realist Theory of Science”, although the arguments for and the presentation of them might be new and somewhat different.